CORPORATE LAW: MANDATORY OFFER REGIME IN NEED OF PRECISE EXEMPTIONS AND LEEWAY - Paul Nkoane (Obiter, 2016)
Mandatory offers are generally envisioned to curb unfair and abusive conduct during and after acquisition of securities in a regulated company. The regime is designed to offer minorities an opportunity to exit the company during takeovers. Mandatory offers are formulated to regulate all acquisitions in the range of the prescribed percentage. Only where the Panel exempts an offeror will the transaction not be covered by the rules of mandatory offers. In keeping with the purpose of the Companies Act, this article is intended to indicate that clear and precise exemptions must form an integral component of this regime.